EFFECTIVENESS OF GROUP GUIDANCE TO IMPROVE STUDENTS’ SOCIAL INTERACTION OF TUNADAKSA GRADE XI SLB NEGERI KOTA BENGKULU ACADEMIC YEAR 2012/2013 - Ariani, Winda Ade (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
Disabled students often feel that they are not accepted in their social environment, for they usually find it hard to adapt or adjust in it. This study is purposed to: (1) to know the description of the social interaction of students with physical disability in SLB Negeri Bengkulu. (2) the differences in the social interaction of disabled students before and after being given the group guidance.This research’s population are 10 students of  XI.D class. The research includes the design of experimental research with the time series experiment using random sampling technique method, in which the questionnaire using Likert Scale models is used as the instrument, then analyzed by the Wilcoxon Signed Ranks Test with SPSS version 16. The author concludes that group counseling is effective to improve the social interaction among the disabled students.mamajitu